Sakamoto days. Vol. 4, Quiet on the train - Suzuki, Yūto (Shonen Jump manga., 2022)
"Kill some time with former hit man Taro Sakamoto! Taro Sakamoto was once a legendary hit man considered the greatest of all time. Bad guys feared him! Assassins revered him! But then one day he quit, got married, and had a baby. He's now living the quiet life as the owner of a neighborhood store, but how long can Sakamoto enjoy his days of retirement before his past catches up to him?! The race to rescue Lu takes Sakamoto and Shin deep into an underground lab. However, they're not the only ones there on a mission--the legendary members of the ORDER are there as well to investigate the mysterious X!"--